2012
DOI: 10.1039/c2nr31077e
|View full text |Cite
|
Sign up to set email alerts
|

Noble metal (Pd, Ru, Rh, Pt, Au, Ag) doped graphene hybrids for electrocatalysis

Abstract: Metal decorated graphene materials are highly important for catalysis. In this work, noble metal doped-graphene hybrids were prepared by a simple and scalable method. The thermal reductions of metal doped-graphite oxide precursors were carried out in nitrogen and hydrogen atmospheres and the effects of these atmospheres as well as the metal components on the characteristics and catalytic capabilities of the hybrid materials were studied. The hybrids exfoliated in nitrogen atmosphere contained a higher amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(116 citation statements)
references
References 22 publications
2
110
0
1
Order By: Relevance
“…Stability of the selected nanohybrids was investigated by alteration of salinity, pH, and temperature. Moreover, results showed that the related Pickering emulsions of the selected nanohybrids have very good stability at 1% salinity, moderate and high (25 C and 90 C) temperatures, and neutral and alkaline (7,10) pH that are suitable for the oil reservoirs conditions. However, contact angle and interfacial tension measurement results showed that the 70% nanoporous graphene/SiO 2 nanohybrid (Method 2) is more e ective in improvement of the stone reservoir wettability alteration from oil-wet to water-wet and can decrease the interfacial tension.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Stability of the selected nanohybrids was investigated by alteration of salinity, pH, and temperature. Moreover, results showed that the related Pickering emulsions of the selected nanohybrids have very good stability at 1% salinity, moderate and high (25 C and 90 C) temperatures, and neutral and alkaline (7,10) pH that are suitable for the oil reservoirs conditions. However, contact angle and interfacial tension measurement results showed that the 70% nanoporous graphene/SiO 2 nanohybrid (Method 2) is more e ective in improvement of the stone reservoir wettability alteration from oil-wet to water-wet and can decrease the interfacial tension.…”
Section: Introductionmentioning
confidence: 95%
“…It has excellent optical, mechanical, and electronic properties [7][8][9][10][11][12][13]. Graphene oxide can be formed with the oxidation of graphene [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Se han explorado materiales híbridos como grafeno dopado con metales nobles para este propósito, sin embargo, estos metales están limitados por su escasa disponibilidad y el elevado costo, [4,5,6]. En este contexto, los metales de transición pueden servir como una alternativa prometedora [7,8,9]. En la búsqueda de nuevos materiales catalíticos los métodos computacionales de primeros principios han demostrado ser útiles herramientas en el diseño racional de catalizadores ya que permiten llegar a resultados y tendencias comparables con datos experimentales, de un modo relativamente rápido, [10].…”
Section: Introductionunclassified
“…There are several approaches to tune graphene electronic transport properties and the work function, including covalent modification of graphene framework [56], deposition of metals to generate Schottky-barrier type carrier injection [55,57], and noncovalent charge-transfer complex formation [58][59][60][61][62]. Due to simplicity and controllability, we choose the latter route and investigated the influence of AuCl 3 doping on self-assembled graphene thin film conductive properties.…”
Section: Au-doping and Stabilitymentioning
confidence: 99%